Biological threats in the 21st century the politics, people, science and historical roots - Lentzos, Filippa (Imperial College Press, 2016)
Biological Threats in the 21st Century offers a fresh understanding of contemporary biological threats to national security. The book provides inspiration and resources for students and researchers, as well as policy makers in government, the public policy sector and the wider community.